2016
DOI: 10.1007/s00405-016-4042-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of septoplasty on pulmonary artery pressure and right ventricular function in nasal septum deviation

Abstract: Nasal septum deviation (NSD) can cause obstruction of the upper airway, which may lead to increased pulmonary artery pressure (PAP) and right ventricle dysfunction. The aim of the present study was to evaluate the effect of septoplasty on right ventricular function and mean PAP of patients with marked NSD. 25 patients with marked NSD (mean age = 31.8 ± 12.3 years) and 27 healthy volunteers (mean age = 34.5 ± 10.8 years) were enrolled. Echocardiography was performed for all subjects and right ventricular functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…They showed that patients with NSD had increased PAB levels and impaired function of the right ventricle compared with the healthy subjects. Moreover, the impaired outcomes improved after septoplasty (8).…”
Section: Discussionmentioning
confidence: 95%
“…They showed that patients with NSD had increased PAB levels and impaired function of the right ventricle compared with the healthy subjects. Moreover, the impaired outcomes improved after septoplasty (8).…”
Section: Discussionmentioning
confidence: 95%
“…In previous studies, it was shown that RV functions recovered and pulmonary artery pressure decreased significantly after surgical correction of upper airway obstruction in patients with adenotonsillar hypertrophy, nasal septum deviation and similar pathologies. [9][10][11][12] To the best of our knowledge, this is the first study in the English literature in which patients operated on for severe NP were evaluated in terms of RV function in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary hypertension increases RV pressure and causes RV hypertrophy, dilatation and finally, RV dysfunction. [12][13][14] There is usually a long asymptomatic period until RV dysfunction develops. [13] When the patient becomes symptomatic, the process is mostly irreversible.…”
Section: Discussionmentioning
confidence: 99%
“…NSD is an expensive medical condition, and also acts as a predisposing factor for other diseases ( Bousquet et al, 2008 ; Fokkens et al, 2012 ). For instance, long-term NSD may indirectly increase the risk of cardiovascular disease ( Ozkececi et al, 2016 ; Uluyol et al, 2016 ). Conservative treatments for NSD have a low benefit likelihood ( Lindsay, 2012 ; Rhee et al, 2014 ; Rudy & Most, 2017 ), and according to studies published in The Lancet in 2019, nasal septoplasty is more effective than non-surgical treatment in adults with NSD ( Van Egmond et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%